Dynamics of Bacterial Root Endophytes of Malus domestica Plants Grown in Field Soils Affected by Apple Replant Disease - Mahnkopp-Dirks, Felix; Radl, Viviane; Kublik, Susanne; Gschwendtner, Silvia; Schloter, Michael; Winkelmann, Traud (Frontiers in Microbiology, 2022)
Apple replant disease (ARD) is a worldwide problem for tree nurseries and orchards leading to reduced plant growth and fruit quality. The etiology of this complex phenomenon is poorly understood, but shifts of the bulk soil and rhizosphere microbiome seem to play an important role. Since roots are colonized by microbes from the rhizosphere, studies of the endophytic microbiome in relation to ARD are meaningful. In this study, culture independent and culture dependent approaches were used in order to unravel the endophytic root microbiome of apple plants 3, 7 and 12 months after planting in ARD-affected soil and ARD-unaffected control soil at two different field sites. Next to a high diversity of Pseudomonas in all soils molecular barcoding approaches revealed an increase in relative abundance of endophytic Actinobacteria over time in plants grown in ARD and control plots. Furthermore, several Amplicon sequence variants (ASVs) linked to Streptomyces, which had been shown in a previous greenhouse ARD-biotest to be negatively correlated to shoot length and fresh mass, were also detected in roots from both field sites. Especially in roots of apple plants from control soil these ASVs increased in their relative abundance over time. The isolation of 150 bacterial strains in the culture dependent approach revealed a high diversity of members of the genus Pseudomonas, confirming the data of the molecular barcoding approach. However, only partial overlaps were found between the two approaches underlining the importance of combining these methods in order to better understand this complex disease and develop possible countermeasures. Overall, this study suggests a key role of Streptomyces in the etiology of ARD in the field.